Current Marketing Practices in the Information Society Era - Ion-Dănuț LIXANDRU; Daniel Nicolae MĂIȚĂ; Daniel ALEXANDRU; Andra Denisa LEUȘTEAN (Revista de Management Comparat International)
This article examines the adaptation of marketing to the evolution of the information society and the impact of advanced digital technologies on marketing strategies. In an era dominated by the rapid flow of information, organizations need to adjust their tactics to respond to the needs and behaviors of modern consumers. The author explores the role of data usage and big data analysis, digital marketing and online influencers, as well as personalization and customer experience as key elements in contemporary marketing. Integrating these aspects into marketing strategies can support building stronger customer relationships, achieving greater relevance in the market, and meeting business objectives in a competitive and dynamic environment. The paper provides a comprehensive perspective on current trends and future directions in modern marketing, highlighting the need for continuous adaptation to technological and social changes in the context of an evolving information economy.